Diversity of reef fishes in trap fishery at Keelakarai, Gulf of Mannar, south-east coast of India - Varghese, Molly; Ranjith, L.; Joshi, K. K. (Indian Journal of Fisheries, 2017)
The diversity of finfishes caught in traps at Keelakarai, Gulf of Mannar was assessed quantitatively and qualitatively for a period of six years from July 2006 to June 2012. Average landing during the period was 109 t per year with maximum of 137 t during 2008-09. Among the 98 species of reef fishes landed, Siganus canaliculatus dominated (28%), followed by Scarus ghobban (21%). During the first two years of the study, S. ghobban dominated over S. canaliculatus and later the trend reversed. Family-wise, maximum contribution was by Siganidae (36%) followed by Scaridae (21%). Seasonally, the major peak was recorded during post-monsoon of 2009. The Shannon index of diversity was maximum during 2007-08. Cluster analysis indicated the highest similarity in species composition between 2010-11 and 2011-12. SIMPER analysis identified 26 species as most significant in creating the observed pattern of similarity for 90% cut off contributions. Ellipse plot showed statistically significant deviation in fish diversity between years. Reef fish landings showed an increasing trend from 2006-07 to 2008-09, a decline afterwards and then almost steady condition prevailed during the last two years of the study which implies that there is no scope for further increase in landings by trap fishery at Keelakarai.